Sloboda mog uma- avangardne umjetnice iz kolekcije Marinko Sudac / : The Freedom of My Mind- Avant-garde Wmone Artists from the Marinko Sudac Collection - Dorotea Fotivec Ocic; Marinko Sudac Foundation (Zagreb; Institute for the Research of the Avant-Garde, 2023)
Published with exhibition organized by The City of Zapresic and Marinko Sudac Foundation, curated by Dorotea Fotivec Ocic.
Croatian; English
Keywords: N5198-5299 Private collections and collectors